Exogenous applications of salicylic acid, ethrel and cycocel: Synergistic effects on yield, quality and storability in Garlic (Allium sativum L.) cv. Ooty 2 - Indhumathi, S; Irene, Vethamoni P; Senthil, A; Vanitha, S; Thamaraiselvi, SP (Plant Science Today, 2024)
Garlic (Allium sativum L.) is a valuable bulb crop, known for its rich bioactive compounds and health benefits. This study aimed to evaluate the impact of various foliar spray treatments on the growth, yield and quality of garlic cv. Ooty 2. The treatments included a control, 100 ppm, 200 ppm and 300 ppm of salicylic acid, cycocel at 1000 ppm and ethrel 200, 300 ppm sprayed at 45 and 60 days after planting. The experiment was conducted using a randomized block design with 7 treatments and 3 replications. Results revealed that salicylic acid 300 ppm increased growth traits followed by ethrel 300 ppm over the control. Cycocel 1000 ppm showed that high bulb yield and less reduction in quality characters viz., TSS (39.2 ?Brix), acidity (0.38 %), ascorbic acid (11.25 mg 100 g-1), total carbohydrate (39.82 g 100 g-1) and phenolics (4.10 mg 100 g-1) content during 3 months storage period, followed by ethrel 300 ppm. Additionally lowest levels of physiological loss in weight (17.47 %), rubbering (5.13 %), rotting (5.88 %) and total loss (23.64 %) was observed compared to all other treatments during the storage period. The results indicate that cycocel at 1000 ppm had the most beneficial effects and can be effectively used to enhance the harvest, post-harvest traits and quality and storability of garlic bulbs.